Syndrome of Inappropriate Antidiuretic Hormone Secretion Associated With Olfactory Neuroblastoma - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2013)
This study reports a patient having olfactory neuroblastoma complicated by syndrome of inappropriate antidiuretic hormone secretion. Olfactory neuroblastoma is a rare tumor that begins in the olfactory membrane. Only 10 cases have been reported previously. Because of having nonspecific symptoms, most patients manifest at an advanced stage at the time of diagnosis. Olfactory neuroblastoma may show local invasion and/or distant metastasis. We demonstrated preoperatively clinical and biochemical parameters consistent with antidiuretic hormone syndrome turned to normal ranges after the treatment. Surgery, chemotherapy, and radiotherapy are the choices of treatment; among these, surgery is an indispensible treatment.
Keywords: Olfactory neuroblastoma; syndrome of inappropriate antidiuretic hormone secretion; esthesioneuroblastoma; sinonasal tumors; SKULL BASE; ESTHESIONEUROBLASTOMA; RADIOTHERAPY; EXPERIENCE; CHEMOTHERAPY; SURVIVAL; TUMORS